2016
DOI: 10.1021/acs.jpclett.6b01839
|View full text |Cite
|
Sign up to set email alerts
|

Size-Dependent Ligand Quenching of Ferromagnetism in Co3(benzene) n + Clusters Studied with X-ray Magnetic Circular Dichroism Spectroscopy

Abstract: Cobalt-benzene cluster ions of the form Co(bz) (n = 0-3) were produced in the gas phase, mass-selected, and cooled in a cryogenic ion trap held at 3-4 K. To explore ligand effects on cluster magnetic moments, these species were investigated with X-ray absorption spectroscopy (XAS) and X-ray magnetic circular dichroism (XMCD) spectroscopy. XMCD spectra yield both the spin and orbital angular momenta of these clusters. Co has a spin magnetic moment of μ = 6 μ and an orbital magnetic moment of μ = 3 μ. Co(bz) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 87 publications
2
38
0
Order By: Relevance
“…46,47 During the preparation of this manuscript S.T. Akin et al 22 reported XMCD measurements for Co 3 Bz + 3 cluster with null spin-magnetic moment. The null signal could be understood as a consequence of the predicted noncollinear character of the local magnetic moments.…”
Section: Final Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…46,47 During the preparation of this manuscript S.T. Akin et al 22 reported XMCD measurements for Co 3 Bz + 3 cluster with null spin-magnetic moment. The null signal could be understood as a consequence of the predicted noncollinear character of the local magnetic moments.…”
Section: Final Remarksmentioning
confidence: 99%
“…By using collinear DFT calculations they tried to explain the origin of the quenched magnetic moment, but the results were highly sensible to the exchange correlation functionals used. 22 Henceforth, the magnetic properties of Co-Bz clusters and their response to magnetic fields require further research.…”
mentioning
confidence: 99%
“…80 It might be particular useful to elucidate the degree of valence electron delocalization, which should have a pronounced effect on electron binding energies and core-level excitation energies via charge screening, 43,81 but also on the quenching of local magnetic moments. 80,[82][83][84][85]…”
Section: Discussionmentioning
confidence: 99%
“…Experimcntatly determined orbital-to-spin magnetic moment ratio as a function of cluster size. For comparison the values for Co;t clusters with n = 2, 3, 10 -15 [18,19,10] and t he value of 0.07 for bulk cobalt [3] are also shown. Note t hat the ratio for the cobalt cation in its [Ar]3d 8 3 F ground state is 1.5 and for the cobalt atom with [Ar]3d 7 4s 2 4 F ground state is 1, both of which ru·e outside the scale that is shown here.…”
Section: X-ray Absorption and Xmcd Spectroscopymentioning
confidence: 99%